(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
Migration management, among others, is one of the challenges Bosnia and Herzegovina and the Western Balkan countries have faced in recent years. The uncertain and complex situation has been exacerbated by the corona virus pandemic, and existing material and human resources are now focused on repairing its consequences. The end of the pandemic remains uncertain, social problems are becoming more complex, and systemic support is needed for a growing number of different vulnerable categories in the country. The protection of human rights and fundamental freedoms is imperative, especially in times of crisis. Although significant activities have been implemented, they are still insufficient to adequately respond to migration management. The support of the international community remains necessary. Multisectoral action, coordination and sharing of experiences should be intensified. The European Commission’s 2021 Report for Bosnia and Herzegovina pointed to very limited progress in migration and asylum management and the need to significantly improve this area, ensure effective coordination and provide sufficient and adequate accommodation capacity. The response to the crisis during the outbreak of COVID-19 was assessed as satisfactory by the European community, and greater spread and more severe consequences for the migrant population were prevented. According to some reports, the rights of minorities and asylum seekers continue to be a serious concern for human rights in Bosnia and Herzegovina. Unaccompanied children face specific challenges and vulnerabilities, and their protection and adequate response to their needs is one of the priorities for future action. Media coverage of migrants needs to be reviewed and directed in a way that is in line with the human rights of vulnerable categories and advocating the necessity of their protection. The media is one of the key links in monitoring the protection of human rights, but also in focusing on areas that require urgent action. Preventive activities should become an integral part of the strategic directions of local and national governments, and the support of the international community, cooperation, adequate assessment and protection of the best interests of all citizens are a prerequisite for social security in Bosnia and Herzegovina.